Spatial distribution of the snow thermal resistance on the Russian territory and its impact on the ground freezing and thawing - N. I. Osokin; A. V. Sosnovskiy (Лëд и снег, 2016)
The effect of the snow cover thermal resistance on dynamics of the ground (soil) freezing and thawing is analyzed with the use of numerical modeling. Model calculations show that when heights and densities of snow covers are different, but their thermal resistances are the same, dynamics of the soil freezing and its temperature regimes are similar. Distribution of the snow cover thermal resistance on the Russia’s territory had been mapped, and areas of equal values of the snow heat insulation were isolated. Using data of meteorological station Коynas (the Arkhangelsk oblast) as an example we demonstrate that influence of increased sum of the air negative temperatures on the soil temperature can be compensated by a decrease in thermal resistance of a snow cover.